Constructing Ag decorated ZnS1-x quantum dots/Ta2O5-x nanospheres for boosted tetracycline removal: Synergetic effects of structural defects, S-scheme heterojunction, and plasmonic effects - Liu, Jing; Ma, Min; Yu, Xin; Xin, Changhui; Li, Mingxue; Li, Shijie (Journal of colloid and interface science, 2022)
[Display omitted] •Ag decorated S-scheme ZnS1-x QDs/Ta2O5-x composites were constructed.•Remarkably enhanced visible-light absorption and photocatalysis.•S-scheme heterostructures, structural defects, and plasmonic effects contribute to charge separation.•Suggested degradation pathways and mechanism. Constructing S-scheme charge transfer pathways is often considered to be an efficient strategy for boosting interfacial charge separation for high-performance photocatalysis, especially for ultrawide bandgap tantalum-based semiconductors. In this work, defects-mediated S-scheme ZnS1-x quantum dots (QDs)/Ta2O5-x composites decorated with Ag were prepared by the modified solvothermal and photoreduction methods and employed for visible-light photocatalytic toxic tetracycline degradation. Compared with commercial Ta2O5, pristine Ta2O5-x microspheres, and ZnS1-x QDs, the prepared Ag/ZnS1-x/Ta2O5-x-1.0% composite showed the highest visible-light photocatalytic performance, and the corresponding reaction rate constant reached as high as approximately 0.02605 min−1, which was 5.97 times of ZnS1-x QDs, 2.63 times of Ta2O5-x, and far better than that of commercial Ta2O5. The main reactive species, photocatalytic mechanism and degradation pathways were also studied. The highly enhanced photocatalytic performance of the Ag/ZnS1-x quantum dots/Ta2O5-x composites could be mainly attributed to the formation of Ag modified S-scheme heterostructures and highly increased surface areas. Current work indicates a high-performance tantalum-based composite for dealing with persistent organic pollutants.